2019
DOI: 10.1016/j.archoralbio.2018.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E, periodontal disease and the risk for atherosclerosis: a review

Abstract: ApoE, chronic periodontitis and atherosclerosis Highlights • Accumulating evidence has demonstrated a relationship between chronic periodontal diseases and atherosclerosis • Periodontal pathogens have been associated with atherosclerosis in apoE knockout mice. • ApoE4 may be a candidate antagonistic pleiotropy gene in periodontal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…17 Studies have shown that ε4 increases the plasma levels of TC and LDL-C, as well as the risk for atherosclerosis. 18,19 Moreover, ε4 carriers have a 40% higher risk of developing ASCVD where treatment with statins is often ineffective, whereas ε2 carriers have been reported to exhibit a higher lipid-lowering effect with statins. 20,21 At 1 month follow-up of our patients, we observed that the levels of TC and LDL-C were significantly lowered with the same dose of statins, although there were no significant differences between the TG and HDL groups.…”
Section: Discussionmentioning
confidence: 99%
“…17 Studies have shown that ε4 increases the plasma levels of TC and LDL-C, as well as the risk for atherosclerosis. 18,19 Moreover, ε4 carriers have a 40% higher risk of developing ASCVD where treatment with statins is often ineffective, whereas ε2 carriers have been reported to exhibit a higher lipid-lowering effect with statins. 20,21 At 1 month follow-up of our patients, we observed that the levels of TC and LDL-C were significantly lowered with the same dose of statins, although there were no significant differences between the TG and HDL groups.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that oxysterols increased the osteogenic activity of PDLSCs, and the expression of ABCA1 increased significantly during osteogenesis [99]. Moreover, APOE-in particular, its isoform 4-was recently proposed to increase the risk of periodontitis [100], and APOE-2 allele is associated with higher prevalence of sporadic PD [101,102]. Thus, the APOE-ABCA1 pathway might play a role in this relationship, mainly within the catabolism of triglycerides and cholesterol, highly associated with PD and periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…To date, some studies have shown that the interaction between T2DM and cardiovascular risk supports the progressive development of vascular injury, which leads to atherosclerosis [10]. Studies have pointed out that ApoE genotype is the main in uencing factor for the development of atherosclerosis [11,12], and differences in ApoE genotype can lead to differences in individual pathogenesis [13]. Therefore, the study on ApoE genotype polymorphism has been paid more and more attention.…”
Section: Discussionmentioning
confidence: 99%